Association Between Household Food Security and Disordered Eating Behaviors Among Young Adults with Diabetes: The SEARCH for Diabetes in Youth Study. (29th May 2020) - Jackson, Emahlea; Liese, Angela; Pihoker, Catherine; Malik, Faisal; Jones-Smith, Jessica; Qu, Pingping; Crow, Scott; Loots, Beth; Reboussin, Beth; Dolan, Lawrence; Igudesman, Daria; Sauder, Katherine; et al.
Abstract: Objectives: Examine the relationship between household food insecurity (HFS; i.e., access to nutritionally adequate and safe food) and disordered eating behaviors (i.e., restriction, bingeing, insulin manipulation, etc.) among a sample of young adults with youth-onset type 1 (T1D) or type 2 diabetes (T2D). Methods: We used cross-sectional data from the SEARCH for Diabetes in Youth Study. Individuals ( n  = 792) ages ≥18 years completed the U.S. Household Food Security Survey Module and the Diabetes Eating Problem Survey-Revised (DEPS-R) between 2016 and 2019. We converted HFS scores to a 10-point scale and dichotomized scores into food secure (HFS ≤ 2.2) vs. food insecure (HFS > 2.2). Multivariable linear regression was used to evaluate the association of HFS with continuous DEPS-R score (i.e., 0–80, with a greater score indicating greater symptoms of disordered eating), adjusting for potential confounders (i.e., sex, age, race/ethnicity, education, household income, insurance, depressive symptoms, and duration of diabetes). We further stratified analyses by diabetes type. Results: Participants were on average 23.8 ± 3.7 years, 59.6% female, 49.6% non-Latino white, and had a mean diabetes duration of 11.5 ± 3.1 years. The overall mean DEPS-R score was 17.3 ± 10.0 points. Mean DEPS-R scores in individuals living in food secure households ( n  = 709) and food insecure households ( n  = 83) were 16.6 ± 9.45 and 23.4 ± 12.4, respectively. The adjusted DEPS-R scores were 3.6 points (95% CI = 1.5, 5.7; P < 0.001) higher in food insecure compared to food secure households. In individuals with T1D ( n  = 600), the adjusted DEPS-R scores were 5.0 points (95% CI = 2.6, 7.4; P < 0.001) higher in food insecure ( n  = 55) compared to food secure ( n  = 545) households. In individuals with T2D ( n  = 192), there was no significant difference in mean DEPS-R scores between food insecure ( n  = 28) versus food secure ( n  = 164) households in unadjusted or adjusted models ( P > 0.05). Conclusions: Lower household food security in young adults with T1D, but not T2D, is associated with increased disordered eating scores. These results may allow clinicians and other public health professionals to target individuals with low household food security as being at higher risk for potential disordered eating, particularly those with T1D. Funding Sources: NIDDK & CDC.